Odontoma associated with mandibular transmigrated canine in a geriatric patient: Second case report. (12th November 2020) - Brooks, John K.; Kim, Eunlim; Tran, Linh T.; Vieira, Christopher A.; Price, Jeffery B.
Abstract: Objective: This report discusses the clinical relevance of a novel case of an odontoma and transmigrated canine in the setting of florid cemento‐osseous dysplasia (COD), hypercementosis and moderate to severe periodontitis in a 66‐year‐old patient. Background: An odontoma may infrequently impede tooth eruption and rarely has been implicated with canine transmigration. COD is a benign fibro‐osseous lesion associated with decreased vascularity and poorer surgical intervention. Materials and methods: A partially edentulous woman, in no acute distress, underwent clinical and radiographic evaluation in pursuit of comprehensive dental care. Results: Radiographic assessment demonstrated multiple occult pathologies of the mandible, including compound odontoma, canine transmigration, florid COD, hypercementosis and moderate to severe periodontitis, a concurrence thought to be previously unreported. Furthermore, the presence of the odontoma and transmigrated canine is apparently the second reported case in the geriatric population. Conclusions: The attending clinician should carefully weigh removal of an impacted and transmigrated canine associated with an odontoma in the setting of COD and compromised bone, particularly in older individuals. When surgical intervention is deferred in these clinical situations, patients should continue to be monitored for clinical and radiographic development of pathologic processes.